Implementing a Large-scale Assessment Survey to Understand the Learning Levels for Policy Implications and to Improve Teaching-Learning - Bhaduri, Indrani (SCHOOL SCIENCE, 2017)
The Ministry of Education (MoE), India, in 2017, conducted the National Achievement Survey (NAS) to understand the learning levels of the students in Classes III, V and VIII, to assist in policy implications and to improve teachingl-earning. The survey tools used competence based multiple test questions, 45 in Classes III and V and 60 in Class VIII in mathematics, language, sciences and social sciences mapping the learning outcomes corresponding to the three grades. Questionnaires pertaining to students, teachers and schools were also used. The sample consisted of 2.2 million students from 1,10,000 schools across 701 districts from all 36 States/UTs. The results were analysed using both the Classical Test Theory (CTT) and the Item Response Theory (IRT). The findings of the survey helped to guide education policy and enabled differential planning at the district level for improving classroom level teaching-learning.